New research on tobacco - Dreher, Uta (Nova Science Publishers, Incorporated, 2020)
New Research on Tobacco summarizes the history of tobacco, providing an overview of the markets, the available products, and manufacturing processes. The authors discuss the current regulatory environment within the U.S., as well as the efforts being made by the Food and Drug Administration to reduce the harm that tobacco products inflict on society. The important discoveries in tobacco research are addressed, and researchers and scientists are encouraged to continue using tobacco as a research tool due to the wealth of existing scientific information about it. The penultimate chapter focuses on electronic nicotine delivery system, also known as vapes, mods, or e-cigarettes, which have become popular over the years. They have tapped into a billion dollar industry and appear to be staying for good in an ever increasing market. The concluding study examines tobacco consumption in India. The findings reveal that the respondents living in rural areas consumed more tobacco than those in urban spaces
Keywords: Tobacco industry -- United States.; Tabac -- Industrie -- États-Unis.; Tobacco industry; United States